A seed is sleepy - Aston, Dianna Hutts; Long, Sylvia (San Francisco : Chronicle Books, 2007)
An informative, yet beautiful, introduction to seeds.
A Junior Library Guild selection.
Keywords: Seeds -- Juvenile literature; Seeds